Postoperative Complications of Patellar Resurfacing In Total Knee Replacement - Shaheen, Ubair Ullah; Janjua, Sarmad Nasir; Iqbal, Shaheen; Noman, Hafiz Muhammad; Ghouri, Qasim Mahmood; Khalid, Muhammad Noman (Journal of Rawalpindi Medical College, 2024)
Objective: TKR followed by patellar resurfacing has been shown of great advantage in literature. This study is done To review post-operative complications among patients, after being treated with patellar resurfacing in total knee repair Method: Prospective continuous study at Orthopaedic Surgery PAEC General Hospital, Islamabad for 6 months Selected sample size is n=58 by simple random sampling( non-probability) Inclusion criteria: Patients under the age group of 18-70 years old of both genders undergone TKR followed by patellar resurfacing, arthritis undergone TKR followed by patellar resurfacing & patellar resurfacing after trauma. Exclusion criteria: Patients undergone TKR with comorbid; diabetes, congestive heart disease, hypertension, neuropathological diseases & renal disorders.& unwilling to participate. Results: The mean age of participants was 44.32 (S.D=3.5) Mean BMI was 29.4 (S.D=3.2). males were 16 while 42 females went under surgery. There was no association seen between BMI and post-op complications Average follow-up was 98 days (58-144). Co-relation between TKR and patellar resurfacing, there was no variation. Among fifty-eight patients patellar fracture, patellar matlracking, aseptic loosening,. Patellar osteonecrosis, polythene wear, Dislocation following total knee arthroplasty, and other hardware mal-function, Overstuffing of the PFJ in postoperative TKA was seen among three people 5.2% of individuals Conclusion: To reduce the danger of additional difficulties, patellar resurfacing must be performed with a high level of accuracy and precision since it is just as crucial as tibiofemoral replacement